ANALISIS STATISTIK UNTUK MENENTUKAN PENGARUH KEMAGNETAN DAN FRAKSI TERHADAP EKSTRAKSI Al2O3 PADA PROSES MAGNETIC SEPARATION - Sri Winarni; Stefanus Suryo; Neneng Sunengsih (PPSDM Geominerba, 2018)
This study examined the statistical analysis on the magnetic separation process of Al2O3 minerals. The experiment was conducted by the Center of Mineral and Coal Technology Research and Development byattempting the magnetic field strength (magnetism) and mineral size (fraction). The measurements made on the magnetic separation process are in the form of percentage of Al2O3content. The aim of this study was to obtain a combination of treatment of the magnetism and fraction factors which produced the best Al2O3 levels. The statistical analysis method used is Anovaand Duncan’s test. The testing of Anova assumptions was carried out and it was found that the assumption of the normality and homogeneity of various residuals was fulfilled, so that the test results were guaranteed valid. The results obtained on the magnetism factor showed that 7500 gauss magnetic field strength produced the highest Al2O3 content with an average of 57.25% and a standard deviation of 1.62. In the fraction factor, the highest Al2O3 content was produced by the fraction -30 + 60 mesh with an average of 57.39% and a standard deviation of 1.79.